Identification of the Feasibility of Retention Ponds as Flood Control and Environmental Quality Improvement in Residential Areas - Fitri Muliani; Mirza Fahmi; Kumita; Zairipan Jaya; Syarwan (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2025)
Environmentally conscious development is essentially a sustainable development process. Rapid urban activity has a positive impact on economic development. One negative impact caused by rapid urban activity is flooding. The high activity of urban communities due to population growth has resulted in a lack of green land and rainwater absorption areas used to provide urban infrastructure and facilities, including water drainage. This also occurs in Bireuen Regency, a Regency in Aceh dominated by office, trade, housing, and residential activities. Kota Juang District is the center of government in Bireuen Regency, which is dominated by residential areas. Based on the results of initial observations conducted in Kota Juang District, many land cover areas cannot absorb water during high rainfall intensity, resulting in waterlogging at road intersections and in office areas and densely populated residential areas. The average water level during high rainfall intensity is in the range of 60-30 cm, causing local flooding. The writing of this article is based on a literature review where the main source of data used is Google Scholar. A qualitative descriptive data analysis method was applied in this study to describe the phenomenon. So, there is an appropriate problem solving regarding retention ponds in residential areas.